Study orientation among high and low achievers in undergraduate students of Medical and Allied health sciences - Muhammad Haris Janjua, Javeria Iqbal, Muhammad Ahmed Naseer, M. Hassaan, Hamza Naeem, M. Zeeshan Sarwar, Syed Asghar Naqi, (Pakistan Journal of Medical & Health Sciences, 2022)
This study was aimed to determine the relationship between study orientation and academic achievements of MBBS and allied health sciences undergraduate students. This cross-sectional survey was conducted in King Edward Medical University, Lahore. The authors selected 450 students using non-probability, convenience sampling. Student of either gender enrolled in MBBS and Allied Health Sciences were included in this study. Study habits were calculated using modified Study Orientation Scale developed on lines of M. Mukhopandy and D.N Sansawal’s Study Habit inventory scale. Quantitative variables were presented as mean ±S.D. Qualitative variables were presented as frequency and percentages. Student were divided into high (CGPA ≥ 3) and low achievers (CGPA < 3). Association of different demographic variables and CGPA with SHI scores was calculated using independent sample t test. P value < .05 was considered significant. Of the 450 respondents, 48 (10.67%) were male and 402 (89.3 %) were female students. Mean age of the participants was 20.98 ± 1.97 years. Majority 331 (73.6%) were Allied Health Sciences (AHS) students. Most of the participants 363 (80.67%) were from urban background while 231 (51.33%) participants were living in hostels. Of the total, 246 (55.4%) participants were labelled as high achievers while 198 (44.6%) were labelled as low achievers. Students with higher CGPA scores were found to have better SHI scores i.e.,113.78 (15.31) as compared to low achievers i.e., 109.56 (16.34) (P value 0.005). Study orientation of students had a significant effect on the performance of students, with high achievers having significantly better SHI scores than their low achiever colleagues so it is recommended that due attention should be given to study habits.